Molar ratio variation on high pressure methanol production: Quantitative safety analysis / Mohd Aizad Ahmad, Anis Syamimi Abd Rashid and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Abd Rashid, Anis Syamimi; Abdul Rashid, Zulkifli (Universiti Teknologi MARA Shah Alam, 2023)
The objective of this research was to conduct a quantitative safety analysis as well as estimate the possible risk of deaths due to methanol reactors at the Labuan process facility in Malaysia. The gathered outcomes included scenarios that occurred, such as toxicity, thermal radiation, and overpressure. The percentage of mortality was determined when a chemical mixture was discharged from nine plants in varying ratios of 1:3, 1:7, and 1:10, and at different operating pressures of 76, 184, and 331 bar, resulting in the occurrence of various events. ASPEN Hysys software was used to compute the mass and volume fraction of a chemical mixture. ALOHA and MARPLOT were also used to gather data on toxicity, thermal radiation, overpressure, and impacted zones. The quantity of chemicals emitted was calculated for three distinct leakage sizes (10 mm, 75 mm, and 160 mm). The findings showed that the plant with 331 bars at a ratio of 1:3 had the highest fatality rate of 16.07 %, which was caused by methanol leakage at night for a leakage size of 160 mm. This work has the potential to lower the number of deaths caused by methanol plants.